2006
DOI: 10.1016/j.virol.2005.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence and genomic organization of hepatopancreatic parvovirus (HPV) of Penaeus monodon

Abstract: We have determined the genome of hepatopancreatic parvovirus (HPV), a minus, single-stranded DNA virus isolated from infected Penaeus monodon in Thailand. Its genome consisted of 6321 nucleotides, representing three large open reading frames (ORFs) and two non-coding termini. The left (ORF1), mid (ORF2), and right (ORF3) ORFs on the complementary (plus) strand may code for 428, 579, and 818 amino acids, equivalent to 50, 68, and 92 kDa, respectively. The 5' and 3' ends of viral genome contained hairpin-like st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 41 publications
1
68
0
Order By: Relevance
“…The results showed that they were 95% identical to the published Thai sequence (Sukhumsirichart et al 2006). When comparing with the sequence of HPVth primers/probe binding sites, there are 3 mismatched nucleotides (all adenine to guanine nucleotide changes) locating at nucleotide position 12 of the forward primer and nucleotide positions 11 and 29 in the probe-binding region.…”
Section: Indonesian Penaeus Monodon Samplesmentioning
confidence: 51%
See 1 more Smart Citation
“…The results showed that they were 95% identical to the published Thai sequence (Sukhumsirichart et al 2006). When comparing with the sequence of HPVth primers/probe binding sites, there are 3 mismatched nucleotides (all adenine to guanine nucleotide changes) locating at nucleotide position 12 of the forward primer and nucleotide positions 11 and 29 in the probe-binding region.…”
Section: Indonesian Penaeus Monodon Samplesmentioning
confidence: 51%
“…MBV is a large (270 脳 72 nm), rod-shaped, enveloped baculovirus with a genome size estimated to be between 80 and 160 kb (Mari et al 1993). However, HPV is a small (22 nm), icosahedral parvovirus that contains a single-stranded DNA genome of ~6 kb (Bonami et al 1995, Sukhumsirichart et al 2006, La Fauce et al 2007a). …”
Section: Introductionmentioning
confidence: 99%
“…6 kb with a hairpin structure at both 5' and 3' ends , Sukhumsirichart et al 2006, La Fauce et al 2007). Based on morphological and biochemical characteristics, HPV is taxonomically placed within the family Parvoviridae .…”
Section: Introductionmentioning
confidence: 99%
“…The Mid ORF could encode a non-structural protein 1 (NS1) with a length of 579 aa (or 578 aa by La Fauce et al 2007). The Right ORF starts 424 nucleotides (nt) downstream from the Mid ORF and may encode a 820 aa polypeptide that consists of a viral capsid protein (Sukhumsirichart et al 2006). One major (57 kDa) and 2 minor (92 and 54 kDa) structural proteins were detected in the viral preparation, indicating a post-translational modification for genesis of the viral capsid protein.…”
Section: Introductionmentioning
confidence: 99%
“…The complete genome of PmDNV isolated from infected P. monodon in Thailand consists of 6321 nucleotides, representing three ORFs and two non-coding termini. ORF3 encodes a capsid protein of approximately 92 kDa, which may later be cleaved after the first or second arginine residue to produce a 57 kDa or 54 kDa structural protein, respectively [82] . MAbs raised against purified PmDNV isolated from Thailand have been produced, four of which react with a 54 kDa protein by Western blotting and to intranuclear inclusion bodies in tubule epithelial cells in PmDNVinfected tissue by immunohistochemistry [83] .…”
Section: Pmdnvmentioning
confidence: 99%